Pengaruh Customer Relationship Management (Crm) Terhadap Kepuasan Customer D’primahotel Tangerang - Hasana, Uswahtun; Saputra, Faisal Tomi; Salsabil, Luna Safitri (Peneliti.net, 2024)
This research aims to find out the influence of Customer Relationship Management (Crm) on D'primahotel Tangerang Customer Satisfaction. The research method used is a quantitative research method with a data collection method, namely a questionnaire. Data collection is carried out by giving several registered and structured questions or a statement to respondents to answer. This research aims to investigate and analyze the impact of Customer Relationship Management (CRM) on the level of customer satisfaction at D'Primahotel Tangerang. Based on the results of statistical tests, it can be obtained that the significance value of the customer relationship management (X) variable for the Customer Satisfaction variable (Y) is 0.000, which means that the significance value obtained is 0.000 < 0.05 and to determine the t table value for this variable is to form equation, where the number of respondents in this study was 100 people. As a result of the data analysis that has been carried out in this research, it can be concluded that in testing using the statistical t test it can be seen that the calculated t value is greater than the t table and it can be concluded that Ho is rejected and Ha is accepted, meaning that Customer Relationship Management (CRM) has a significant effect significant impact on d'primahotel Tangerang customer satisfaction. Customer relationship management (CRM) has a positive effect on customer satisfaction, which means that if CRM d'primahotel Tangerang does not improve processes and serve customers well, then customer satisfaction will decrease further. And vice versa if CRM d'primahotel Tangerang.